Polyclonal immunoglobulin response of thymic, hepatic and splenic lymphocytes from fetal, germ-free and conventionally reared pigs to different B-cell activators - Cukrowska, B; Sinkora, J; Reháková, Z; Splíchal, I; Tucková, L; Barot-Ciorbaru, R; Bianchi, A T; Lodinová-Zádníková, R; Tlaskalová-Hogenová, H (Folia microbiologica, 1995)
Immunoglobulin (Ig) response to different polyclonal B-cell activators was measured by ELISA in cell culture media of thymocytes, splenocytes and liver cells isolated from pig fetuses, 8-d-old germ-free piglets and conventionally reared pigs. Both in fetal and in postnatal life polyclonally stimulated lymphocytes were found to produce predominantly the IgM isotype; the first IgM formation was detected in 50-d-old fetal liver (gestation in pigs lasts 114 d). Surprisingly, 73-d-old fetal thymic cells were shown to be induced to Ig synthesis and secretion. In contrast to splenocytes of the same age, which secreted exclusively IgM, fetal thymocytes produced IgM, IgG and IgA. Polyclonally stimulated splenic cells as compared with thymic cells started to produce IgA later in fetal ontogeny, whereas the IgG response was not detectable in splenic cell culture media during the whole embryonal development and appeared only after birth. The earliest and the highest Ig stimulation was found after cultivation of lymphocytes with Nocardia delipidated cell mitogen. Interestingly, the moderate stimulatory effect of 65-kDa heat shock protein (Hsp-65) in polyclonal IgM response of fetal splenocytes was observed. We showed that thymic B lymphocytes represent probably the first maturing B cell population detectable in fetal life, which is able to differentiate after polyclonal stimulation into IgM as well as IgA and IgG producing cells.
Keywords: Liver; Organic Chemicals; Animals; gnotobiologické modely; Enzyme-Linked Immunosorbent Assay; plod; lipopolysacharidy; Mitogens; játra; slezina; bakteriální proteiny; Antibody Formation; Bacterial Proteins; Lymphocyte Activation; chaperon hsp60; aktivace lymfocytů; mitogeny; Fetus; tvorba protilátek; prasata; Chaperonins; Organ Culture Techniques; mitogeny líčidla amerického; Lipopolysaccharides; Thymus Gland; orgánové kultury - kultivační techniky; chaperoniny; Germ-Free Life; ELISA; Chaperonin 60; Swine; thymus; B-Lymphocytes; Spleen; Pokeweed Mitogens; B-lymfocyty; organické látky; zvířata